Análisis Preliminar del Strip-slot Complementario en Tecnología Stripline - Hernández Escobar, Alberto; Abdo-Sánchez, María Elena; Camacho-Peñalosa, Carlos (My University, 2017)
A stripline-fed slot antenna configuration is proposed using planar technology. Its main advantages are the broad impedance bandwidth available and the radiation in only one half-space, which are obtained with the use of its complementary strip element and the stripline technology, respectively. A lattice network circuit model is proposed to understand the behavior of the structure and to design the radiating element. Its capabilities are highlighted through a design, which shows a simulated bandwidth of 8 GHz in the 10 GHz band and an unidirectional broadside radiation pattern.
Keywords: Antenas; Stripline; Antena de ranura